Surfing among species, populations and morphotypes: Inferring boundaries between two species of new world silversides (Atherinopsidae) - González Castro, Mariano (2016)
Atherinopsidae are widespread freshwater and shallow marine fish with singular economic importance. Morphological, genetical and life cycles differences between marine and estuarine populations were already reported in this family, suggesting ongoing speciation. Also, coexistence and interbreeding between closely related species were documented. The aim of this study was to infer boundaries among: (A) Odontesthes bonariensis and O. argentinensis at species level, and intermediate morphs; (B) the population of O. argentinensis of Mar Chiquita Lagoon and its marine conspecifics. To achieve this, we integrated, meristic, Geometrics Morphometrics and DNA Barcode approaches. Four groups were discriminated and subsequently characterized according to their morphological traits, shape and meristic characters. No shared haplotypes between O. bonariensis and O. argentinensis were found. Significative-meristic and body shape differences between the Mar Chiquita and marine individuals of O. argentinensis were found, suggesting they behave as well differentiated populations, or even incipient ecological species. The fact that the Odontesthes morphotypes shared haplotypes with both, O. argentinensis and O. bonariensis, but also possess meristic and morphometric distinctive traits open new questions related to the origin of this morphogroup.